Control interno y la gestión administrativa de la Municipalidad Distrital de Punchana de la región Loreto, periodo 2022 - Soto Shuña, Leo Alexander (2023)
The research deals with internal control and administrative management, likewise, the research is of a quantitative, descriptive and correlational type, elaborated through a non-experimental design, for which its main objective is to "determine the relationship between internal control and administrative management in the district municipality of Punchana, Loreto 2022", counting as the study population the 269 workers of the municipality of Punchana. In this sense, the investigation determined that the level of internal control is mostly Regular at 47.80%, Good at 44.03%, and Bad at 8.18%, on the other hand, Administrative Management is mostly Good level at 47.17%, Regular in 45.91% and Bad in 6.92%. Finally, according to the correlation coefficient between internal control and administrative management equal to Rho=0.850 and the value of Sig. (bilateral)=0.000, it is concluded that there is a high and direct relationship between internal control and administrative management. in the district municipality of Punchana in the Loreto region, period 2022.